Abundance of skeletobionts on Middle Devonian brachiopods from Madène el Mrakib, Morocco (Eifelian–Givetian transition, Taboumakhloûf Formation) and R code for analysing colonization patterns - Zatoń, Michał; Nawrot, Rafał (PANGAEA, 2024)
Brachiopod shells were collected from the scree directly adjacent to the exposures in Madène el Mrakib in order to describe skeletobiont diversity, abundance and colonization patterns, and their relation to host shell morphology. The studied specimens originate from the fossiliferous, thin-bedded, 2.5 m-thick nodular limestone (mudstone to packstone) belonging to Taboumakhloûf Formation and placed at the transition of the uppermost Eifelian (ensensis Zone) and lowermost Givetian (hemiansatus Zone) based on conodont dating. Further details can be found in Zatoń et al. (2022). The brachiopod specimens, both articulated shells and isolated valves, were collected randomly without regard for the presence of skeletobionts. Each brachiopod specimen (separately dorsal and ventral valves) was inspected under a binocular microscope and each skeletobiont was determined to the lowest possible taxonomic level and counted. For colonial organisms, each individual colony was counted as one specimen. Among brachiopod specimens without any skeletobionts only well preserved and articulated shells are included in the dataset. The external surface area of the selected, well-preserved and complete shells of the five dominant brachiopod species was measured using a square-gridded plankton net (1 x 1 cm), with a mesh size of 1 mm2.
Keywords: Bioerosion; Brachiopoda; Devonian; Encrustation; Palaeoecology; Sclerobionts; Shell size; Skeletobionts